Removal of final wash in chicken slaughter process does not affect microbiological quality of carcasses - Gomes da Silva, Erton; Tadielo, Leonardo Ereno [UNESP]; Bellé, Thiago Henrique; Rodrigues dos Santos, Emanoelli Aparecida; Schmiedt, Jhennifer Arruda; Possebon, Fábio Sossai [UNESP]; Pereira, Juliano Gonçalves [UNESP]; Bersot, Luciano dos Santos (Elsevier, 2021)
Water is used in several stages of the technological process of chicken slaughter. Since it is a finite natural resource, the objective of this study was to evaluate the effect of reducing the water flow in the final wash on the superficial microbial contamination of chicken carcasses in a slaughterhouse. The experimental design was completely randomized (3 × 10 × 3), and comprised the evaluation of three treatments, i.e., absence of water (T1), flow of 1 L per carcass (T2), and flow of 1.5 L per carcass (T3), with 10 repetitions performed in triplicates. A total of 240 samples were obtained at three points in the slaughter line: before (A, n = 90) and after (B, n = 60) the final washing of the carcasses and after cooling (C, n = 90). Analyses of counts of aerobic mesophilic microorganisms, enterobacteria, total coliforms, and Escherichia coli were performed. The final wash reduced the microbiological contamination of the carcasses but suffered direct interference from the pre-cooling system (P > 0.05), which canceled the reduction. Hence, the final wash step may be removed without affecting the microbiological quality of the carcasses, making it possible to reduce water consumption and effluent generation.
Keywords: Escherichia coli; Indicator microorganism; Slaughterhouse; Water